Effective quality improvement of thromboprophylaxis in acute medicine. Issue 5 (8th March 2011) - Clark, Barbara M; d'Ancona, Grainne; Kinirons, Mark; Hunt, Beverley J; Hopper, Adrian
Abstract : Introduction: The Health Select Committee Report on the prevalence of venous thromboembolism (VTE) in 2005 suggested that poor awareness of the risks of VTE contributed significantly to mortality and morbidity in hospitalised patients. It recommended that all hospitalised patients should undergo a VTE risk assessment. In 2006, an audit in medical patients at Guy's and St Thomas' NHS Foundation Trust (GSTFT) revealed a lack of documentation of VTE risk assessment and poor use of thromboprophylaxis in 'at risk' patients. In 2007, the GSTFT 'Venous Thromboembolism in Adult Medical Inpatients' guideline was approved. The aim was to achieve a thromboprophylaxis culture within Acute Medicine and, in doing so, achieve a high adherence rate. Methods: The guideline was launched and implemented using a multidisciplinary and multiple intervention approach involving education and feedback, IT intervention, verbal and written reminders, regular audit and process redesign. Results: An audit in 2008 showed that the rate of adherence had increased from 56% preguideline to 96%. However, a repeat audit in 2009 suggested that even though the majority of patients were receiving appropriate thromboprophylaxis, risk assessment documentation was poor. This resulted in treatment being provided to some low-risk patients when it was not required. Conclusion: In conclusion, the most effective means of achieving VTE guideline adherence is to establish a thromboprophylaxis culture. This can be accomplished through a multiple intervention and continuous feedback approach. However, it is essential to ensure that a comprehensive VTE risk assessment is carried out to ensure that those not requiring treatment do not receive it unnecessarily.